A non-interventional comparative study between medical and dental undergraduates regarding their knowledge, attitude and practice of antibiotic use in a tertiary care teaching rural hospital: emphasis on WHO fact-sheets - Dass, Ervilla; Patel, Aneri; Patel, Huzaifa; Patel, Dhruvesh; Patel, Himanshi; Patel, Harvi; Patel, Bhavya (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The threat of antibiotic resistance is rapidly progressing and intensifying. The awareness generation of antibiotic use, its seriousness and significance are the first step towards restricting its progress. It is in this regards that this comparative questionnaire-based study was conducted. Methods: The knowledge, attitude and practice (KAP) among medical and dental students of a tertiary care teaching rural hospital was assessed. Before initiating the study, their written consent was taken, and 125 structured questionnaires were distributed to medical and dental students. Data collected was further entered in Microsoft excel sheet and further comparison of KAP between them was analysed. Results: The results were depicted in percentage. Regarding the indiscriminate and injudicious use of antibiotics can lead to prolongation of illness, the medical students were more aware 82.4% compared to the dental 65.6%. When asked about additional burden of medical cost to the patient, the medical students responded with yes 88.8% and dental student’s response of yes was 47.22%. Also, medical 90.4% students had heard about antibiotic resistance and 60.8% from dental students, which implies that UG students should be made more aware of antibiotic resistance and its consequences. Conclusions: Thus, the results of the study give useful information about the knowledge, attitudes and practices of medical and dental students, that can be further utilized to plan suitable educational interventions that target at improving the knowledge for prescribing antimicrobial medicines. This can further help in minimizing the development of bacterial resistance.